“A cross-sectional study of burnout among Australian general practice registrars” - Rebekah Hoffman; Judy Mullan; Andrew Bonney (BMC Medical Education, 2023)
Abstract Objective(s) To identify if gender and parenting factors are associated with burnout in Australian general practice (GP) registrars. Design Cross sectional study. The main outcome measure was the Maslach Burnout Inventory, included as part of the GPRA (General Practice Registrars Australia) biannual online survey. Participants: GP registrars, 2019 cohort, undertaking fellowship training in Australia. Results In 2019 a total of 366 GP registrars completed the online survey. Over 75% of registrars experienced moderate to high levels of burnout (emotional exhaustion scale). Several demographic factors were associated with an increased risk for reporting higher levels of burnout. Increasing age was associated with lower levels of personal accomplishment (P-value < 0.01), being female was associated with higher levels of emotional exhaustion (p-value < 0.001) and increasing numbers of children were associated with lower levels of burnout, independent of hours worked (p-value < 0.001). Conclusion This study suggests that being a parent is associated with a reduced risk of burnout, irrespective of hours worked. However, being female and increased age were associated with increased levels of burnout. With increasing numbers of females entering medical training, and the decreasing desirability of general practice training, this paper reviews the complexities around parenting during training and associations with burnout. There is a need to examine this interaction further to understand the causation for these findings, and to ensure appropriate policies, opportunities and workplace supports are developed to ensure GP training is optimised to attract and support the next generation.